Crystal structure of poly[diaqua-bis(μ2-5-((pyridin-4-yl-methyl)amino)benzene-1,3-dicarboxylato-κ 2 N:O)cadmium(II)], C28H26CdN4O10 - Zhang Lai-Jun; Weng Wen-Fang; Huang Shuai; Ye Xiao-Qing; Deng Yuan-Yuan; Lang Jia-Yi; Yin Qing; Ding Jun-Jie (Zeitschrift für Kristallographie - New Crystal Structures)
C28H26CdN4O10, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 5.7700(12) Å, b = 10.190(2) Å, c = 12.160(2) Å, α = 70.38(3)°, β = 84.72(3)°, γ = 81.63(3)°, V = 665.6(3) Å3, Z = 1, R gt(F) = 0.0272, wR ref(F 2) = 0.0602, T = 293 K.